Amino Acid Substitutions and Differential Gene Expression of Outer Membrane Proteins in Adherent-Invasive Escherichia coli - Camprubí-Font, Carla; Ruiz del Castillo, Belén; Barrabés, Silvia; Martínez-Martínez, Luis; Martinez-Medina, Margarita (Frontiers in Microbiology, 2019)
Variations in the sequence and/or the expression of outer membrane proteins (OMPs) may modulate bacterial virulence. OmpA and OmpC have been involved in the interaction of adherent-invasive Escherichia coli (AIEC) strain LF82 with intestinal epithelial cells. Scarce data exist about OMPs sequence variants in a collection of AIEC strains, and no study of OMPs expression during infection exists. We aimed to determine whether particular mutations or differential expression of OMPs are associated with AIEC virulence. The ompA, ompC and ompF genes in 14 AIEC and 30 non-AIEC strains were sequenced by Sanger method, and the protein expression profile was analyzed by urea-SDS-PAGE. Gene expression was determined during in vitro bacterial infection of intestine-407 cells by RT-qPCR. The distribution of amino acid substitutions in OmpA-A200V, OmpC-S89N, V220I and W231D associated with pathotype and specific changes (OmpA-A200V, OmpC-V220I and D232A, OmpF-E51V and M60K) correlated with adhesion and/or invasion indices. OMPs protein levels did not differ according to pathotype. Higher ompA and ompF expression levels were reported in AIEC growing in the supernatants of infected cultures compared with those in non-AIEC strains (p<0.030). Interestingly, AIEC decreased OMPs expression when growing in association with cells (p<0.032), whereas non-AIEC strains did not significantly alter OMPs expression under this condition (p>0.577). In conclusion, the AIEC-associated OMPs amino acid substitutions identified herein could facilitate a better interaction with the host, and OMPs gene expression changes at different stages of AIEC infection suggest that these proteins may play a distinct role in adhesion and/or in intracellular survival.